The Good Boss - Walker, Kate (Ascent Audio, 2021)
When it comes to a woman's day-to-day experience and her career trajectory, one key player has the most significant impact: her boss. If we really want to support women in the workplace, managers must step up. The good news is that many of the things you can do to be a better manager for women are easy. In The Good Boss, CEO and business consultant Kate Eberle Walker offers timely, tactical advice based on her experience coaching managers, as well as the lessons she learned working her own way up the corporate ladder. Eberle Walker outlines nine straightforward rules that any manager can follow to help the women on their team-whether they oversee one, one hundred, or one thousand employees. You'll learn: how to build stronger working relationships by being your authentic self; how she balances work and family, and what you can do to help; what to do (and what not to do) when a new mother returns to work; how to identify and deal with problematic comments and behaviors from her coworkers; and when is the right time to be a tough boss and how to navigate difficult conversations. Eberle Walker also shares insights from CEOs across a range of industries who use creative, forward-thinking methods to support women throughout an entire organization.